Drug side effects on KIR2.1 and hERG cardiac channels - Coelho, Ana Filipa Caldeira Calado Fagundes (2011)
The correct understanding of cardiac electrophysiology, action potential and behavior of all ionic channels nvolved in cardiomyocyte membrane polarization/depolarization has become a Holy Grail to reach a full explanation of cardiac arrhythmias and development of new harmacological therapies. In this context, there are two most relevant ionic channels: the inward rectifier potassium channel KIR2.1 and the voltage-dependent hERG, which appear to contribute assertively to the terminal phase of repolarization of the action potential (phase 3) and for the stabilization of the resting membrane potential of cardiomyocytes through its currents – inward rectifier (IK1) and rapid delayed rectifier (IKr), respectively. Additionally, KIR2.1 and hERG inherent pathologies can arise by intracellular traffic problems, caused not only by genetic mutations, but also by interactions with particular drugs. Actually, antimicrobial or antidepressant drug side effects on the cardiovascular system may be related with interactions on KIR2.1 and/or hERG, especially in overdose situations (acute effects). However, little is yet known about these mechanisms of interference. In this study we examined, among others, the effects of chronic administration of pentamidine (antimicrobial), 2EVK (pentamidine analog) and fluoxetine (“Prozac”, antidepressant) in HEK-KWGF and HEK-HERG cells. Unexpectedly, pentamidine and 2EVK revealed to have entirely different actions at cellular level. Pentamidine and fluoxetine proved to be strong inhibitors of hERG maturation, while 2EVK had no effect on this process. On the other hand, KIR2.1 protein levels increased with 2EVK and fluoxetine (1.52 ± 0.29 and 1.54 ± 0.16, respectively) and decreased with pentamidine (0.90 ± 0.20) after a 24-hour incubation. During this period and for all drugs, KIR2.1 remains at the cell membrane and/or dispersed throughout the cytoplasm. Interestingly, after 48h in the presence of fluoxetine, a strong polarized accumulation of KIR2.1 around the nucleus was reported for the first time, suggesting perhaps the involvement of endoplasmic reticulum or Golgi apparatus. Despite these effects on KIR2.1 and hERG may explain, in part, their side effects, the involvement of other receptors and ion channels, cannot be, currently, excluded.